Pandemics of the poor and banking stability - Lagoarde-Segot, Thomas; Leoni, Patrick L. (Journal of Banking & Finance, 2013)
We first develop a theoretical model that shows that the likelihood of a collapse of the banking industry of a developing country increases, as the joint prevalence of large pandemics such as AIDS and malaria increases. We also show that the optimal bank reserves increase as the prevalence increases. In the empirical part of the paper, we consider a large dataset of developing countries, and we exhibit a causality effect from combined prevalence to deposit turnover, as well as causality effect from an increase of combined prevalence to an increase in bank reserves. Those empirical facts therefore support our theoretical findings.